Cognitive load influences oculomotor behavior in natural scenes - Walter, Kerri; Bex, Peter (Scientific reports, 2021)
Cognitive neuroscience researchers have identified relationships between cognitive load and eye movement behavior that are consistent with oculomotor biomarkers for neurological disorders. We develop an adaptive visual search paradigm that manipulates task difficulty and examine the effect of cognitive load on oculomotor behavior in healthy young adults. Participants (N = 30) free-viewed a sequence of 100 natural scenes for 10 s each, while their eye movements were recorded. After each image, participants completed a 4 alternative forced choice task in which they selected a target object from one of the previously viewed scenes, among 3 distracters of the same object type but from alternate scenes. Following two correct responses, the target object was selected from an image increasingly farther back (N-back) in the image stream; following an incorrect response, N decreased by 1. N-back thus quantifies and individualizes cognitive load. The results show that response latencies increased as N-back increased, and pupil diameter increased with N-back, before decreasing at very high N-back. These findings are consistent with previous studies and confirm that this paradigm was successful in actively engaging working memory, and successfully adapts task difficulty to individual subject’s skill levels. We hypothesized that oculomotor behavior would covary with cognitive load. We found that as cognitive load increased, there was a significant decrease in the number of fixations and saccades. Furthermore, the total duration of saccades decreased with the number of events, while the total duration of fixations remained constant, suggesting that as cognitive load increased, subjects made fewer, longer fixations. These results suggest that cognitive load can be tracked with an adaptive visual search task, and that oculomotor strategies are affected as a result of greater cognitive demand in healthy adults.